PENGARUH RETURN ON EQUITY, GROSS PROFIT MARGIN, DAN TOTAL ASSET TURNOVER TERHADAP PERTUMBUHAN LABA PADA PT SIANTAR TOP TBK PERIODE 2014 – 2023 - Khanifah Firlia Naftiar; Hestu Nugroho Warasto (Journal of Research and Publication Innovation, 2024)
Gross Profit Margin, Total Asset Turnover, on Profit Growth both partially and simultaneously. The research method used is descriptive with a quantitative approach, using secondary data from PT's financial reports. Siantar Top Tbk. period 2014-2023. Data analysis methods include classical assumption tests, multiple linear regression analysis, hypothesis testing T-test, F-test and coefficient of determination test (R2). The t test results show that Return On Equity has a value of tcount < ttable (-1.813 < 2.447) and a significant value greater than sig. 0.05 or (0.120 > 0.05) this means that Return On Equity has no significant effect on Profit Growth. Gross Profit Margin has a value of tcount > ttable (3.338 > 2.447) and a significant value smaller than sig. 0.05 or (0.016 < 0.05) this means that Gross Profit Margin has a significant effect on Profit Growth. Total Asset Turnover has a value of tcount > ttable (3.436 > 2.447) and a significant value smaller than sig. 0.05 or (0.014 < 0.05) this means that Total Asset Turnover has a significant effect on Profit Growth. From the results of the F test, the sig. of (0.019 < 0.05) and the value of Fcount > Ftable (7.503 > 4.74) shows that simultaneously Return On Equity, Gross Profit Margin and Total Asset Turnover influence Profit Growth. The results of the Coefficient of Determination Test (R2) show an Adjusted R-Square value of 0.684, which means that together Return On Equity, Gross Profit Margin, and Total Asset Turnover contribute 68.4% while 31.6% is explained by the variable others not examined in this study.